Breastfeeding and HIV-Infected Women in the United States: Harm Reduction Counseling Strategies. (24th April 2014) - Levison, Judy; Weber, Shannon; Cohan, Deborah
Abstract : Despite recommendations to the contrary, some HIV-infected women in the United States will choose to breastfeed. We offer a harm reduction model for those women with HIV who are considering breastfeeding. Abstract : Social and cultural forces have led some human immunodeficiency virus (HIV)–infected women to question the recommendation in the United States not to breastfeed. Without an open dialogue, women may choose to breastfeed exclusively or intermittently and not disclose this to their provider. We review the evidence from global studies of the risks of breastfeeding among HIV-infected mothers and propose a harm reduction model for women considering breastfeeding.